Henri Bergson : key writings / edited by Keith Ansell Pearson and John Mullarkey ; mélanges translated by Melissa McMahon. - Bergson, Henri, 1859-1941 (Athlone contemporary European thinkers., 2002)
This volume brings together generous selections from his major texts: Time and Free Will, Matter and Memory, Creative Evolution, Mind-Energy, The Creative Mind, The Two Sources of Morality and Religion and Laughter. In addition it features material from the Melanges never before translated in English, such as the correspondence between Bergson and William James. The volume will be an excellent textbook for pedagogic purposes and a helpful source book for philosophers working across the analytic/continental divide.